Work and Welfare - Solow, Robert M. (Book collections on Project MUSE., 2001)
The Nobel Prize-winning economist Robert Solow directs his attention here to one of today's most controversial social issues: how to get people off welfare and into jobs. With characteristic eloquence, wit, and rigor, Solow condemns the welfare reforms recently passed by Congress and President Clinton for confronting welfare recipients with an unworkable choice--finding work in the current labor market or losing benefits. He argues that the only practical and fair way to move recipients to work is, in contrast, through an ambitious plan to guarantee that every able-bodied citizen has access to.